Aggravation of Reflux Finding Score (RFS) after thyroidectomy - Yoon, Hyung-Joon (PLoS One, 2021)
Laryngopharyngeal reflux (LPR) has been suggested as a possible cause of post-thyroidectomy syndrome. However, the pathophysiology and relationship between thyroidectomy and LPR have not been well investigated. We aimed to evaluate the correlation between thyroidectomy and LPR by assessing changes in LPR-related symptoms and laryngoscopic findings before and after thyroidectomy. Ninety-five patients who underwent thyroidectomy with or without central neck dissection were included. The reflux finding score (RFS) and reflux symptom index (RSI) were investigated one day before surgery and two, four, six, and twelve months after surgery. The RFS scores increased significantly after thyroidectomy and decreased to the preoperative level 12 months after surgery. The RSI scores increased after surgery and decreased gradually by 12 months postoperatively, although it was not statistically significant. The RSI and RFS scores improved with the administration of proton pump inhibitors. In conclusion, LPR-related laryngoscopic findings were exacerbated after uncomplicated thyroidectomy. Further studies using pH-monitoring and esophageal manometry are required to investigate the possible deterioration of LPR itself and the UES pressure after thyroidectomy.